Understanding the R882H mutation effects of DNA methyltransferase DNMT3A: a combination of molecular dynamics simulations and QM/MM calculations. Issue 54 (3rd October 2019) - Liu, Lanxuan; Shi, Ting; Houk, Kendall N.; Zhao, Yi-Lei
Abstract : The AML-related high-frequent R882H mutation of DNA (cytosine-5)-methyltransferase 3A (DNMT3A), a key enzyme for de novo epigenetic methylation in human beings, was characterized by a disturbing conformation of S -adenosylmethionine (SAM). Abstract : DNA (cytosine-5)-methyltransferase 3A (DNMT3A), a key enzyme for de novo epigenetic methylation in human beings, was reported to undergo an R882H mutation in approximately 25% of M4/M5 subtype acute myeloid leukemia (AML) patients. In this work, a combination of classical molecular dynamics (MD) simulations and QM/MM calculation methods was utilized to reveal the molecular mechanism behind the activity attenuation caused by R882H mutation. We found that R882H mutation induces a "folded" conformation in the methyl donor S -adenosylmethionine (SAM) through different types of hydrogen bond formation at the terminal carbonyl oxygen atom and the hydroxyl O3′ atom of the ribose ring on SAM, with Arg891 as a mediator. Energetically, both the pre-reaction state (PRS) and transition state (TS) were stabilized in the R882H mutant. However, the energy barrier of the rate-determining step from the PRS to the TS was calculated to be roughly 1.0 kcal mol −1 larger in the R882H mutant than the WT. Also, a dynamic transformation occurred along the helix where R882H was located, tending to manifest in a quasi-"Newton's cradle" manner from the mutational site to the active site residues of DNMT3A. Our computational results provided molecular insights into the pathogenic R882H mutation and advanced the understanding of its mechanism.